Sosialisasi Antikorupsi di Kecamatan Kampar Kiri dengan Dampak Ekonomi Ummat - Hendra Eka Saputra; Putri Lukmanasari; Dela Lutfia; Alfa Rezki (Lembaga Pengembangan Kinerja Dosen, 2026)
Kampar Kiri District faces challenges in the form of low public understanding of anti-corruption values, which has an impact on hampering the development of the people's economy and transparency of local governance. This Community Service (PKM) activity aims to increase critical public awareness and internalize the value of integrity in sharia-based economic activities. The implementation method is carried out through a participatory approach that includes socialization, education on moral-religious values, and interactive discussions. The activity was held on August 21, 2025, at the KUD Lipat Kain Hall, attended by 100 participants, and fully supported by the Kampar Regency Education Office. The results of the service show a positive response from the local government and high enthusiasm from the younger generation in maintaining integrity. Through the involvement of expert speakers from the Riau Anti-Corruption Counseling Forum and the Kampar Inspectorate, the community gained a comprehensive understanding of the dangers of corruption from a legal and religious perspective. This program has succeeded in laying the foundation for the formation of an honest, transparent, and accountable social ecosystem to realize a blessed community economy.